НAВОИЙ ВA ҚОДИРИЙ ИЖОДИДA ДЎСТЛИК МAВЗУСИ - Ёрқиной Aбдумуталиб қизи, Исмонова (Educational Research in Universal Sciences, 2022)
The article explores and compares the concept of friendship, especially in the works of Alisher Navoi and Abdullah Qadiri, with the examples of the role and importance of the concept of friendship in the eyes of the two great writers.